Baseline total metabolic tumour volume on 2-deoxy-2-[18F]fluoro-d-glucose positron emission tomography-computed tomography as a promising biomarker in patients with advanced non–small cell lung cancer treated with first-line pembrolizumab. (June 2021) - Dall'Olio, Filippo G.; Calabrò, Diletta; Conci, Nicole; Argalia, Giulia; Marchese, Paola Valeria; Fabbri, Francesca; Fragomeno, Benedetta; Ricci, Dalia; Fanti, Stefano; Ambrosini, Valentina; Ardizzoni, Andrea
Abstract: Introduction: Immune checkpoint inhibitors (ICIs) have become the standard of care in the management of advanced non–small cell lung cancer (NSCLC). Nevertheless, only a small proportion of patients benefit from ICIs. The aim of the present study is to assess whether 2-deoxy-2-[18F]fluoro-d-glucose positron emission tomography-computed tomography ( [18F]FDG-PET/CT)–derived parameters may be used as biomarkers in patients with advanced NSCLC receiving first-line pembrolizumab. Materials and methods: This is a monocentric retrospective cohort study including patients with advanced NSCLC (stage IV) and Programmed death-ligand 1 (PD-L1) expression ≥50% treated with pembrolizumab. A control group of patients treated with epidermal growth factor receptor (EGFR) inhibitors for EGFR-mutated NSCLC was also enrolled. Only patients with a positive [18F]18F-FDG PET/CT result within 60 days from treatment initiation were included.Total metabolic tumour volume (tMTV) was calculated for each lesion using a dedicated software (PET VCAR; GE Healthcare), which semiautomatically delineates the tumour's contours with a maximum standardised uptake value (SUVmax) threshold of 42% within the lesion. tMTV was obtained summing each lesion's MTV. Potential prognostic parameters for overall survival (OS) were analysed (tMTV, SUVmax, bone/liver metastasis, neutrophil:lymphocyte ratio ≥4, Eastern Cooperative Oncology Group performance status ≥2, lactate dehydrogenase above the upper limit of normal). Results: Overall, 34 patients treated with first line-pembrolizumab and 40 patients treated with EGFR tyrosine kinase inhibitors were included. In the pembrolizumab group, the median follow-up was 20.3, while the median OS was 4.7 months (95% confidence interval [CI] = 0.3–9.1) for patients with tMTV ≥75 cm 3 vs not reached (NR) for patients with tMTV <75 cm 3 (95% CI = NR–NR; hazard ratio [HR] = 5.37; 95% CI = 1.72–16.77; p = 0.004). No difference was found in the control group (HR = 1.43; 95% CI = 0.61–3.34; p = 0.411). Conclusion: Our data suggest that tMTV ≥75cm 3 can be used as a prognostic biomarker of poor outcomes in patients with PD-L1–high advanced NSCLC treated with first-line pembrolizumab. This information could be useful for the selection of patients who may require the addition of chemotherapy to pembrolizumab. Highlights: Patients with high total metabolic tumour value (tMTV) have limited benefit from immune checkpoint inhibitors alone including first-line pembrolizumab. There is no correlation with outcomes in epidermal growth factor receptor–mutated patients treated with tyrosine kinase inhibitors. A score comprising Eastern Cooperative Oncology Group performance status and neutrophil:lymphocyte ratio could be promising. Further research should focus on cut-off or nomogram establishment. Patients with high tMTV could benefit from combination therapy.